Pyrolysis of Aloe vera leaf wastes for biochar production: Kinetics and thermodynamics analysis - Kocer, Anil Tevfik; Erarslan, Azime; Ozcimen, Didem (ELSEVIER, 2023)
The large waste potential of biomass, which is used extensively industrially, is a problem that needs to be solved both environmentally and economically. In this context, the conversion of these wastes into valuable solid products by thermochemical conversion processes is considered a very important alternative. In this study, it was aimed to examine the pyrolytic behavior of Aloe vera leaf waste, determine the pyrolysis kinetic parameters and characterize the biochar obtained as a result of pyrolysis at different temperatures. The pyrolytic behavior of this waste at temperatures between 25 and 600 degrees C and heating rates of 5, 10, 20 and 40 degrees C min-1 were investigated by thermogravimetric method. The pyrolysis kinetic parameters of these wastes were calculated using the Kissinger-Akahira-Sunosa (KAS) and Flynn-Wall-Ozawa (FWO) methods. According to the results obtained, the pyrolysis of Aloe vera waste took place in 3 stages (moisture removal, devolatilization and char formation) and approximately 65% of the mass was removed from the structure. The activation energy values calculated by KAS and FWO methods for the devolatilization and char formation stages were found to be approximately 185 kJ mol-1 and 335 kJ mol-1, respectively. According to the kinetic and characterization results obtained, it has been understood that Aloe vera leaf wastes are a very suitable source for biochar production and biochar obtained can be evaluated in different areas such as adsorption, agriculture and combustion.
Keywords: Carbonization; Biochar; Thermogravimetry; Aloe vera; Pyrolysis kinetics; BIOMASS; LIGNIN; CARBON; CELLULOSE; MECHANISM; ENERGY; WOOD; Agriculture